Filantropi Islam melalui Program Kerja Lembaga Amil Zakat Dompet Dhuafa dalam Meningkatkan Pemberdayaan Masyarakat di Sulawesi Selatan - Femy Farasiah, Tenri femy; Anwar, Nurfiah; Darussalam, Andi Zulfikar (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of the zakat institution over the years brings about a change. One of the institutions, the zakat managing organization (opz), dhuafa sulawesi's purses, which released programs related to the empowerment of society. Researchers chose dhuafa's purse-department because of one of the institutions that developed specifically in its economic empowerment program. The study has a purpose to know the implications of islamic philanthropy through opz's work program to promote public empowerment. Research methods used are qualitative descriptive methods, which learn of the phenomenon of observing islamic philanthropy through opz's action program to promote empowerment. Research object of the amil zakat (laz) purses dhuafa sulawesi south (sulsel). Studies study that dhuafa sulsel's wallet laz made a positive impact on people's empowerment.